Proceso de enseñanza aprendizaje y su relación con la conservación del medio ambiente en el 1er grado “A” en la I.E N°00622 del centro poblado El Porvenir - Amasifuen Amasifuen, Witler (2012)
The research aims to determine the correlation between the teaching-learning process and its relationship to environmental conservation in the first grade "A" in the area of Science, Technology and Environment in the Educational lnstitution No. 00622, the Center village "El Porvenir" - Rioja district, 2011. The study is important because it allows to know the manifestations of the relationship between the teaching-learning process in preserving the environment. The main objective of this study was to determine the relationship between the teaching-learning process with the conservation of the environment in the first grade students "A" in the area of Science, Technology and Environment in the Educational lnstitution No. 00622, the Center village "El Porvenir" - Rioja district, 2011, and the specific objectives were to analyze the process of teaching and learning in first grade "A", analyze the conservation of the environment in the first grade "A" and establish the relationship between the teaching-learning process with the conservation of the environment in the first grade "A". The teaching-learning process is supported by the Ministry of Education, the National Basic Education, Santillana, Sanchez, Taylor and Esquén, who claim that the process is performed to develop skills in students, and environmental conservation based by Jimenez, Sanchez, Yarlequé, Munoz, who claim that it is necessary to preserve our environment for a better life. With the theoretical support we have the following hypothesis: There is a relationship between the teachinglearning process with the conservation of the environment in the first grade "A" in the area of Science, Technology and Environment in the Educational lnstitution No. 00622, the Center village "El Porvenir" - Rioja district, 2011. Methodologically, the research design was descriptiva and correlational with a sample of 23 students in first grade "A" high school educational institution No. 00622, and in the process of statistical analysis it was found that one accepts the hypothesis or central research with a 95% confidence, the same as is shown by the xiii graph of the Gauss curve and the value that was obtained from the Pearson correlation coefficient being mean and a positive correlation is explained by the 52.69% population.